On our backs : entertainment for the adventurous lesbian. (San Francisco : Blush Entertainment, 1989)
Fonds Suzan Daniel (FSD)
Periodiciteit : tweemaandelijks
Redactie : 526 Castro, San Francisco CA 94114
Engels
Periodiek